Interventions to improve the implementation of evidence-based healthcare in prisons: a scoping review - Blackaby, Jenna; Byrne, Jordan; Bellass, Sue; Canvin, Krysia; Foy, Robbie (Health & justice, 2023)
Background There are challenges to delivering high quality primary care within prison settings and well-recognised gaps between evidence and practice. There is a growing body of literature evaluating interventions to implement evidence-based practice in the general population, yet the extent and rigour of such evaluations in incarcerated populations are unknown. We therefore conducted a scoping literature review to identify and describe evaluations of implementation interventions in the prison setting. Methods We searched EMBASE, MEDLINE, CINAHL Plus, Scopus, and grey literature up to August 2021, supplemented by hand searching. Search terms included prisons, evidence-based practice, and implementation science with relevant synonyms. Two reviewers independently selected studies for inclusion. Data extraction included study populations, study design, outcomes, and author conclusions. We took a narrative approach to data synthesis. We followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance for scoping reviews. Results Fifteen studies reported in 17 papers comprised one randomised controlled trial, one controlled interrupted time series analysis and 13 uncontrolled before and after studies. Eight studies took place in the US and four in the UK. Ten studies evaluated combined (multifaceted) interventions, typically including education for staff or patients. Interventions most commonly targeted communicable diseases, mental health and screening uptake. Thirteen studies reported adherence to processes of care, mainly testing, prescribing and referrals. Fourteen studies concluded that interventions had positive impacts. Conclusions There is a paucity of high-quality evidence to inform strategies to implement evidence-based health care in prisons, and an over-reliance on weak evaluation designs which may over-estimate effectiveness. Whilst most evaluations have focused on recognised priorities for the incarcerated population, relatively little attention has been paid to long-term conditions core to primary care delivery. Initiatives to close the gaps between evidence and practice in prison primary care need a stronger evidence base.